(untitled) (The Review of Diabetic Studies, 2024)
Background Patient safety involves preventing preventable harm and minimizing healthcare risks via organized activities fostering safe cultures and processes. Globally, one in ten acute care patients experiences harm, with 30-50% preventable, mainly from medication errors and procedural issues, as highlighted by WHO and IOM reports like "To Err is Human." Multidisciplinary teams counter silos by integrating nursing surveillance, pharmacy stewardship, assistant support, and nutritional optimization.​ Methods This narrative synthesis draws from global evidence-based literature, including systematic reviews, studies, and guidelines on PubMed, Scopus, and similar databases. It examines distinct roles, interprofessional dynamics, challenges like communication gaps, and strategies such as TeamSTEPPS and IPE, focusing on contributions to error reduction across settings.​ Results Nurses lead vigilance, infection control, and handovers; pharmacists drive MTM, ASPs, and error interception (up to 50%); health assistants aid monitoring, falls prevention, and escalation; nutritionists prevent malnutrition (affecting 50% inpatients) and allergies. Teams using SBAR/ISBAR reduce adverse events by improving communication and outcomes like readmissions.​ Conclusions Integrated roles significantly bolster safety, but barriers like shortages and silos persist; recommendations include IPE, simulations, AI tools, and policies for role clarity to guide evidence-based, patient-centered care.​